Leaf venation of living species of Persea (Lauraceae), with taxonomic and nomenclatural notes - Rodrigues De Moraes, Pedro Luis [UNESP] (Magnolia Press, 2022)
With the aim of recognizing and identifying both fertile and sterile specimens of Persea, leaf venation patterns of 54 taxa were studied, 36 of them being described and illustrated for the first time. Analysis of a matrix of 12 leaf venation characters and 31 states distinguishes the taxa and can be used to detect misidentifications. Additionally, lectotypes for the names Laurus cordata, L. lingue (second-step), L. subcordata, Menestrata racemosa, Persea cordata var. microphylla, P. donnell-smithii, P. laevigata, P. lingue, P. nivea and P. rugosa are designated, and the identity of Persea microneura and the status of P. jariensis are clarified.
Keywords: Laurales; leaf venation; morphology; Neotropical flora; nomenclature; taxonomy